2014
DOI: 10.1177/147470491401200507
|View full text |Cite
|
Sign up to set email alerts
|

Do Orgasms Give Women Feedback about Mate Choice?

Abstract: The current study represents a preliminary investigation of the extent to which female orgasm functions to promote good mate choices. Based on a survey of heterosexual female college students in committed relationships, how often women experienced orgasm as a result of sexual intercourse was related to their partner's family income, his self-confidence, and how attractive he was. Orgasm intensity was also related to how attracted they were to their partners, how many times they had sex per week, and ratings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 30 publications
5
44
0
Order By: Relevance
“…This is broadly referred to as the sire-choice hypothesis of female orgasm. In keeping with this theory, a number of studies have observed that orgasm rate is higher with more attractive and masculine partners (Andersson, 1994;Gallup Jr, Ampel, Wedberg, & Pogosjan, 2014;Grammer, Fink, Møller, & Thornhill, 2003;Shackelford et al, 2000), though it is unsurprising that women are more likely to orgasm with males they are more attracted to.…”
Section: Genetic Benefits and Parental Investmentmentioning
confidence: 92%
See 4 more Smart Citations
“…This is broadly referred to as the sire-choice hypothesis of female orgasm. In keeping with this theory, a number of studies have observed that orgasm rate is higher with more attractive and masculine partners (Andersson, 1994;Gallup Jr, Ampel, Wedberg, & Pogosjan, 2014;Grammer, Fink, Møller, & Thornhill, 2003;Shackelford et al, 2000), though it is unsurprising that women are more likely to orgasm with males they are more attracted to.…”
Section: Genetic Benefits and Parental Investmentmentioning
confidence: 92%
“…Additionally, Gallup Jr et al (2014) found women reported greater orgasm frequency when their partner's family income was higher, suggesting a role of resource provision potential. The case of the female orgasm is far from closed, however, and there a number of considerations to be taken into account.…”
Section: Genetic Benefits and Parental Investmentmentioning
confidence: 92%
See 3 more Smart Citations